Influence of Age on the Diagnosis of Myocardial Infarction. Issue 15 (15th September 2022) - Lowry, Matthew T.H.; Doudesis, Dimitrios; Wereski, Ryan; Kimenai, Dorien M.; Tuck, Christopher; Ferry, Amy V.; Bularga, Anda; Taggart, Caelan; Lee, Kuan K.; Chapman, Andrew R.; Shah, Anoop S.V.; Newby, David E.; et al.
Abstract : Background: The 99th centile of cardiac troponin, derived from a healthy reference population, is recommended as the diagnostic threshold for myocardial infarction, but troponin concentrations are strongly influenced by age. Our aim was to assess the diagnostic performance of cardiac troponin in older patients presenting with suspected myocardial infarction. Methods: In a secondary analysis of a multicenter trial of consecutive patients with suspected myocardial infarction, we assessed the diagnostic accuracy of high-sensitivity cardiac troponin I at presentation for the diagnosis of type 1, type 2, or type 4b myocardial infarction across 3 age groups (<50, 50–74, and ≥75 years) using guideline-recommended sex-specific and age-adjusted 99th centile thresholds. Results: In 46 435 consecutive patients aged 18 to 108 years (mean, 61±17 years), 5216 (11%) had a diagnosis of myocardial infarction. In patients <50 (n=12 379), 50 to 74 (n=22 380), and ≥75 (n=11 676) years, the sensitivity of the guideline-recommended threshold was similar at 79.2% (95% CI, 75.5–82.9), 80.6% (95% CI, 79.2–82.1), and 81.6% (95% CI, 79.8–83.2), respectively. The specificity decreased with advancing age from 98.3% (95% CI, 98.1–98.5) to 95.5% (95% CI, 95.2–95.8), and 82.6% (95% CI, 81.9–83.4). The use of age-adjusted 99th centile thresholds improved the specificity (91.3% [90.8%–91.9%] versus 82.6% [95% CI, 81.9%–83.4%]) and positive predictive value (59.3% [57.0%–61.5%] versus 51.5% [49.9%–53.3%]) for myocardial infarction in patients ≥75 years but failed to prevent the decrease in either parameter with increasing age and resulted in a marked reduction in sensitivity compared with the use of the guideline-recommended threshold (55.9% [53.6%–57.9%] versus 81.6% [79.8%–83.3%]. Conclusions: Age alters the diagnostic performance of cardiac troponin, with reduced specificity and positive predictive value in older patients when applying the guideline-recommended or age-adjusted 99th centiles. Individualized diagnostic approaches rather than the adjustment of binary thresholds are needed in an aging population.